2016
DOI: 10.1002/cne.24083
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of astrocyte and NG2 cell insertion at the node of ranvier

Abstract: The node of Ranvier is a functionally important site on the myelinated axon where sodium channels are clustered and regeneration of action potentials occurs, allowing fast saltatory conduction of action potentials. Early ultrastructural studies have revealed the presence of “glia” or “astrocytes” at the nodes. NG2 cells, also known as oligodendrocyte precursor cells or polydendrocytes, which are a resident glial cell population in the mature mammalian central nervous system that is distinct from astrocytes, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 61 publications
(87 reference statements)
1
52
0
Order By: Relevance
“…In line with this view, confocal and electron microscopy studies showed that NG2 glia establish physical contacts with functionally relevant neuronal domains, including dendrites [41,42], somata [14,41,43,44], nodes of Ranvier [45,46] and synapses [47,48] (Figure 1C). About 30-50% of the nodes are contacted by both NG2 glia and astrocyte processes in the optic nerve, corpus callosum, and spinal cord of young adult rodents.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…In line with this view, confocal and electron microscopy studies showed that NG2 glia establish physical contacts with functionally relevant neuronal domains, including dendrites [41,42], somata [14,41,43,44], nodes of Ranvier [45,46] and synapses [47,48] (Figure 1C). About 30-50% of the nodes are contacted by both NG2 glia and astrocyte processes in the optic nerve, corpus callosum, and spinal cord of young adult rodents.…”
Section: Introductionsupporting
confidence: 62%
“…Notably, while NG2 glia are never coupled via gap-junctions [59,60], some of them express connexin 32 [61] and partly couple to mature OLs [62]. Further, electron microscopy analysis showed that NG2 glia processes often contact the paranodal loops of myelin [46]. These data suggest a privileged communication between NG2 glia and other elements in the oligodendroglial lineage.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations